Real-World Analysis of Adherence to Abemaciclib and Endocrine Therapy in Women with HR+/HER2− Breast Cancer - Maria Rosaria Valerio; Federica Martorana; Maria Vita Sanò; Daniela Sambataro; Gianmarco Motta; Lucia Motta; Giuliana Pavone; Vittorio Gebbia; Giuseppa Scandurra (Biomedicines)
Background: Adherence to oral anticancer therapies among breast cancer patients is an often-overlooked issue. A lack of patient compliance can be caused by several factors, and may hinder the efficacy of prescribed medication, leading to a shorter than expected survival. In this context, few data about adherence to CDK4/6 inhibitors in real-world practice are available. We report here the results of a retrospective analysis of adherence to abemaciclib plus endocrine therapy in a cohort of women with hormone receptor-positive (HR+), epidermal growth factor 2 negative (HER2−) breast cancer. Methods: Abemaciclib adherence was computed as the ratio between the total number of cycles/months that medication was supplied and the months between the first and the last prescription. The proportion of Days Covered (PDC) ranged from 0 to 1. A score of 0.8 (i.e., 80% adherence rate) was the cutoff used to classify the patients as adherent (0.8 ≤ PDC ≤ 1) or non-adherent (0 ≤ PDC < 0.8). The received dose intensity was also calculated. Results: The abemaciclib pharmacy claims of 100 women with HR+/HER2− breast cancer were retrieved. Most patients (91%) were treated in the advanced setting. Abemaciclib was more frequently taken with an aromatase inhibitor (63%) than with fulvestrant (27%). In this population, the adherence rate was high (92.25% + 1.939 SD). The proportion of non-adherent patients taking abemaciclib with PDC <0.8 was 12%. There was a significative correlation between the occurrence of side effects and the use of <5 drugs for non-oncological illnesses, probably reflecting concomitant non-oncological diseases. Conclusions: Adherence to abemaciclib-based therapy is high in a real-life setting, pending the adequate and proactive management of patients. The careful evaluation of patients and detailed information about expected adverse events are essential to ensure adherence to this antineoplastic agent.